Tunable annealing effect to enhance structural and magnetic properties of spinel cobalt magnesium ferrite nanoparticles - Preanka Mondal; Sumi Akter; Probal Roy; Iftakhar Bin Elius; M. N. I. Khan; S. S. Sikder (AIP Advances, 2024)
Cobalt magnesium ferrite nanoparticles, with the chemical formula Co0.5Mg0.5Fe2O4 (CMFO), were synthesized via co-precipitation and subjected to annealing at 200–800 °C with a step size of 200. Thermal analysis for the as-dried sample was investigated through thermogravimetric analysis (TGA) and differential thermal analysis (DTA). The presence of a plateau region in the DTA curve above 366 °C, combined with the slight weight loss noted in the TGA curve, indicates that the ferrite sample, specifically CMFO, has successfully transitioned into its final phase. X-ray diffraction and Fourier transform infrared spectroscopy (FTIR) analysis unveiled the formation of spinel CMFO NPs belonging to the Fd-3m space group. The Williamson–Hall method showed particle size increasing from 8.20 to 52.15 nm and tensile microstrain decreasing from 6.90 to 1.84 × 10−3 with higher annealing temperatures, noted by the shift of the (311) plane. TEM images confirmed the formation of smaller nanoparticles with minimal agglomeration. Particles of nearly uniform size are achieved at the optimum annealing temperature of 600 °C, owing to its narrow distribution profile. The experimental magnetization data were analyzed using the Langevin function and the law of approach to saturation to determine the saturation magnetization, spanning from 15.46 to 43.90 emu/g. The magnetic characteristics of the annealed samples exhibited a rise in coercive force, reaching up to 349.74 Oe with the elevation of the annealing temperature. The range of attributes exhibited by CMFO makes it highly advantageous for various applications, including sensor technology, high-frequency devices, and energy storage devices.